2020
DOI: 10.4028/www.scientific.net/kem.840.10
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness Adsorption of Au(III) and Cu(II) Ion by Mangosteen Rind (<i>Garcinia mangostana </i>L.) Using Point of Zero Charge Calculation

Abstract: Adsorption of Au(III) and Cu(II) by mangosteen rind adsorbent had been carried out. Mangosteen rind has several functional groups including –OH phenolics, ‒C=C‒ aromatics, and ethers. Dried mangosteen rind which was obtained from maceration was used to determine Point of Zero Charge (PZC). The most effective pH adsorption was determined by mixing adsorbent with Au(III) or Cu(II) solutions with various pH. The adsorption capacity was affected by the interaction between adsorbent and adsorbate. The solid adsorbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…GME has a net negative charge, it may electrostatically repel other negatively charged groups on the nanoparticle surface, causing them to become more exposed and contributing to a more negative charge. 39–42 Fig. 2D showed that the GME-loaded niosomes were stable at room temperature on the day of production.…”
Section: Discussionmentioning
confidence: 96%
“…GME has a net negative charge, it may electrostatically repel other negatively charged groups on the nanoparticle surface, causing them to become more exposed and contributing to a more negative charge. 39–42 Fig. 2D showed that the GME-loaded niosomes were stable at room temperature on the day of production.…”
Section: Discussionmentioning
confidence: 96%
“…The optimum pH of Au(III) and Ag(I) adsorption were 2 and 6, respectively. Our previous research showed that the Point of Zero Charge (pH PZC) of mangosteen rind adsorbent was 3.7 [26]. Below the pH of PZC, the adsorbent tends to be positively charged and could interact electrostatically with AuCl4at pH = 2 condition.…”
Section: Optimal Ph Condition Of Au(iii) and Ag(i) Adsorptionmentioning
confidence: 99%
“…At pH = 2, Au(III) is negatively charged in the form of tetrachloroaurate(III) ions ([AuCl4] -), while the adsorbent surface is protonated and has a positively-charged surface. In an acidic solution, the possibility of electrostatic interaction between the functional group of adsorbent and [AuCl4]increases [26]. Ag(I) has a positive charge at a pH of 2-6.…”
Section: Optimal Ph Condition Of Au(iii) and Ag(i) Adsorptionmentioning
confidence: 99%